Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.4 Derivatives of Logarithmic Functions - 6.4 Exercises: 49

Answer

$y'=x^{sinx}(\frac{sinx}{x}+lnx cosx)$

Work Step by Step

Given: $y =x^{sinx}$ Taking logarithmic on both sides of the function $y =x^{sin x}$ $lny=sinx .lnx$ Take implicit differentiation with respect to $x$. Apply product rule of differentiation. $\frac{d}{dx}(lny)=\frac{d}{dx}(sinx. lnx)$ $\frac{1}{y}\frac{d}{dx}(y)=sinx\frac{d}{dx}(lnx)+lnx\frac{d}{dx}(sinx)$ $\frac{d}{dx}(y)=y[sin\times(\frac{1}{x})+lnx(cosx)]$ Hence, $y'=x^{sinx}(\frac{sinx}{x}+lnx cosx)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.